Pengembangan Sistem Absensi Berbasis GPS Perangkat Mobile Pada Diskominfo Kota Metro - Bagus Abadi; Rakhmat Dedi Gunawan (Journal of Data Science and Information Systems, 2023)
Along with the rapid development of information technology, online attendance has now become a widely used method for conducting online attendance via websites and applications. One example is the Metro City Diskominfo, a regionally owned company which has the task of administering government affairs in the field of communications and information technology. For the Metro area, attendance at the Metro City Communication and Information Department is still done manually by hand, using a hard attendance sheet. For this reason, research was carried out to develop a GPS-based attendance system for mobile/Android devices at metro city communication and information services. Design using UML and the RAD (Rapid Application Development) development method were used to build this attendance system, with a testing method using ISO 25010 which consists of Functionality and Realability aspects. The overall test results for ISO 25010 received a score of 96.12%, which based on the criteria was rated Very Good and it can be said that the installed system meets requirements.